2008
DOI: 10.1245/s10434-008-9810-8
|View full text |Cite
|
Sign up to set email alerts
|

REG Iα is a Reliable Marker of Chemoradiosensitivity in Squamous Cell Esophageal Cancer Patients

Abstract: REG Ialpha expression in squamous cell esophageal carcinoma may be a reliable marker of chemoradiosensitivity. We anticipate that it will enable us to provide more appropriate and individualized treatment to patients of advanced esophageal squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Hayashi et al reported that Reg IA expression might be a marker of long-term survival in patients with locally advanced thoracic esophageal squamous cell carcinoma treated with neoadjuvant definitive chemoradiotherapy followed by planned esophagectomy; they observed that patients with Reg IA-positive tumors were responsive to the chemoradiothrapy, which often provided a complete response and longterm survival (109).…”
Section: Mitogenesis and Cancermentioning
confidence: 99%
“…Hayashi et al reported that Reg IA expression might be a marker of long-term survival in patients with locally advanced thoracic esophageal squamous cell carcinoma treated with neoadjuvant definitive chemoradiotherapy followed by planned esophagectomy; they observed that patients with Reg IA-positive tumors were responsive to the chemoradiothrapy, which often provided a complete response and longterm survival (109).…”
Section: Mitogenesis and Cancermentioning
confidence: 99%
“…In chemotherapy, cells were treated with cisplatin (Nihonkayaku Co., Tokyo, Japan) at concentration of 1.0 or 10 µM. Chemosensitivity was assessed by Cell Counting Kit-8 (WST-8 cleavage; Dojindo, Mashikimachi, Japan) as described previously (23). The cell viability after the chemotherapy for the cells was evaluated with the WST-8 cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that REG1A is a reliable sensitivity marker in ESCC patients (clinical T4) treated with neoadjuvant CRT [33] or definitive CRT [34]. We also recently showed that among stage II and III ESCC patients treated with esophagectomy followed by adjuvant chemotherapy, OS, DSS and DFS were all significantly better in REG1A-positive than REG1A-negative patients [35].…”
Section: Positive Biomarkers In Tissue Examinationmentioning
confidence: 99%